The European and Japanese outbreaks of H5N8 derive from a single source population that has most likely been dispersed along the long distance bird migratory flyways - Dalby,Andrew; Iqbal,Munir (PeerJ PrePrints, 2015)
The origin of recent parallel outbreaks of the high pathogenicity H5N8 avian flu virus in Europe and in Japan can be traced to a single source population, which has most likely been spread by migratory birds. By using Bayesian coalescence methods to analyze the DNA sequences of the virus to find the times for divergence and combining bird migration data we can show the most likely locations and migratory pathways involved in the origin of the current outbreak. This population was most likely located in the Siberian summer breeding grounds of long-range migratory birds. These breeding grounds provide a connection between different migratory flyways and explain the current outbreaks in remote locations. By combining genetic methods and epidemiological data we can rapidly identify the sources and the dispersion pathways for novel avian influenza outbreaks.
Keywords: High pathogenicity avian influenza; HPAI; H5N8; migratory birds; Siberia; Korea; Bayesian; coalescence